Perempuan Single Parent pada Era Digitalisasi; Studi Komunikasi Budaya atas Perubahan Zaman dan Pandangan Masyarakat - Ulfi Nurfaiza (Keraton: Journal of History Education and Culture, 2025)
The development of the digital era has brought significant changes in people's perspectives and communication patterns, including for women with single-parent status. In the past, particularly during the patriarchal era, cultural norms and values tended to place single-parent women in a more challenging position, often accompanied by negative stigma. According to data from DataIndonesia.id, the number of single-parent women in Indonesia in 2021 was higher than that of widowed men. Women who experienced separation, whether due to divorce or the death of a spouse, accounted for 12.83% of the population, whereas men in the same situation only made up 4.32%. The social transformation brought about by the digital era reflects that the increasing number of single-parent women goes hand in hand with greater opportunities for them to develop themselves, including in economic aspects. This study focuses on understanding the identity of single-parent women in the digital era through three key concepts: externalization, objectivation, and internalization. Using a qualitative method with a social construction approach, this research collects data through in-depth interviews, observations, and documentation. The findings indicate that single-parent women perceive their status as a learning experience in independence, allowing them to work and pursue careers without limitations. Additionally, they can leverage social media as a platform to enhance their quality of life and expand their social networks. Society has also begun to acknowledge that single-parent women are now more confident and comfortable with their status. With advancements in technology and information, being a single parent is no longer viewed as something to be feared or constantly stigmatized. Instead, the meaning of this status has evolved into something more positive and inclusive.